Coordinated expansion planning problem considering wind farms, energy storage systems and demand response - Hamidpour, Hamidreza; Aghaei, Jamshid; Pirouzi, Sasan; Niknam, Taher; Nikoobakht, Ahmad; Lehtonen, Matti; Shafie-khah, Miadreza; Catalão, João P.S. (Energy (Oxford), 2022)
During the recent years, the power system has entered a new technological era. The trends associated with increased commitment to wind farms (WFs) and energy storage systems (ESSs) as well demand side flexibility require disruptive changes in the existing power system structures and procedures. Being at the heart of a paradigm shift from passive users of the grid to active prosumers, storage owners and demand responsive actors, this paper expresses a flexible coordinated power system expansion planning (CPSEP) while considering local WFs, ESSs and incentive-based demand response programs (DRPs). This model minimizes the summation of the expansion planning, operation and reliability costs while taking the network model based on AC optimal power flow constraints, and the reliability and flexibility considerations into account. The proposed framework is firstly formulated by mixed integer non-linear programming (MINLP), then to have a well-handed optimization model it is converted to mixed-integer linear programming (MILP). Additionally, the uncertainties of load, energy price, maximum WF generation and availability/unavailability of the network equipment are included in the proposed model where the first three parameters are modeled based on the bounded uncertainty-based robust optimization (BURO), and the scenario-based stochastic programming (SBSP) is used to model the last uncertain parameter. Finally, the proposed method is examined on several test networks to assess the performance of the proposed framework for flexi-reliable transmission network operation and planning. •This paper expresses a reliable, flexible coordinated power system expansion planning.•Local wind farms, energy storage system and demand response programs are considered.•The model minimizes the summation of the expansion planning, operation and reliability costs.•The performance of the strategy efficiency is assessed for enhancing network operational indices.